2013
DOI: 10.1089/tmj.2012.0243
|View full text |Cite
|
Sign up to set email alerts
|

Enabling the Mission Through Trans-Atlantic Remote Mentored Musculoskeletal Ultrasound: Case Report of a Portable Hand-Carried Tele-ultrasound System for Medical Relief Missions

Abstract: Modern medical practice has become extremely dependent upon diagnostic imaging technologies to confirm the results of clinical examination and to guide the response to therapies. Of the various diagnostic imaging techniques, ultrasound is the most portable modality and one that is repeatable, dynamic, relatively cheap, and safe as long as the imaging provided is accurately interpreted. It is, however, the most user-dependent, a characteristic that has prompted the development of remote guidance techniques, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Another study from India assessed the feasibility of cervical ultrasound to detect cervical spine fractures in children . Hand‐carried ultrasound has been successfully used for surgical patient selection across a broad spectrum of diseases, such as abdominal tumours and congenital malformations, as well as for telemedicine‐guided diagnosis in rural areas .…”
Section: Resultsmentioning
confidence: 99%
“…Another study from India assessed the feasibility of cervical ultrasound to detect cervical spine fractures in children . Hand‐carried ultrasound has been successfully used for surgical patient selection across a broad spectrum of diseases, such as abdominal tumours and congenital malformations, as well as for telemedicine‐guided diagnosis in rural areas .…”
Section: Resultsmentioning
confidence: 99%
“…The fellow can continue mastering educational skills when not physically present using well-described do-it-yourself methods of remote monitoring or new technologies that offer teleguidance features. 20,21 • Develop novel teaching opportunities. Fellows may give virtual presentations to residents and rotators during weekly conferences.…”
Section: Fellowsmentioning
confidence: 99%
“…Initial experiences have shown that smartphones are incredibly powerful and might enable global telemedical outreach on an unprecedented scale. 8 Traditionally, Canadians have welcomed a presence in international security missions, and this presence has often been heavily weighted to emphasize medical support in multinational military collaborations. Providing the backbone for a temporary or better permanent telementoring network infrastructure might conceivably be a deliverable that would fit well with Canada's geopolitical resources and philosophies and a task that might further justify the existence of subspecialist physicians with the CF.…”
mentioning
confidence: 99%